The evolution of performance indicators in high-intensity and high-speed training for boys aged 10 to 13, with varying levels of physical activity - Chzhu Khuasin,; Nyu Yindon,; Vrublevskiy E.P. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to discern the effects of age on the performance metrics of speed and power-speed fitness in boys aged 10 to 13, with varying levels of physical activity. Methods and structure of the study. The students of the school in Qinhuangdao (China) took part in the scientific work. Starting at the age of 10, 83 students were tested for three years at the end of the school year. At the same time, 42 boys were engaged in the school athletics section, and the rest did not play sports. The dynamics of speed and speed-strength abilities were determined using tests that are widely described in the specialized literature and recommended for assessing the physical fitness of schoolchildren of various ages [1, 5, 7]. Results and conclusions. Additional and purposeful motor activity contributes to a faster mastery of the required level of physical fitness by boys aged 10-13 years, and the predominant effect on their motor abilities, which are at the stage of accelerated age development, leads to significant shifts in the development of the latter. To increase the speed abilities of boys, the most favorable age is 10-11 years old, and speed and strength - 12-13 years old.